Comparison of the pharmacokinetic profiles of three triterpenoids after oral administration of a cucurbitacin tablet and nanosuspension by UHPLC-MS/MS - Zhang, Chun-nan; Wang, Zhi-bin; Du, Rui-tong; Zhang, Shu-lu; Wang, Chu-qiao; Wang, Meng; Wu, Li-hong; Yang, De-qiang; Wang, Chen (Frontiers in Pharmacology, 2025)
IntroductionCucurbitacin, a class of triterpenoid compounds isolated from Pedicellus Melo, possesses various biological activities and is the primary active component of cucurbitacin tablets (CUT) used to treat chronic hepatitis and primary liver cancer. Nanosuspensions can potentially improve the oral bioavailability of pharmacopotent substances. This is the first study comparing the pharmacokinetics of three cucurbitacin triterpenoids (cucurbitacin B [CuB], cucurbitacin D [CuD], and cucurbitacin E [CuE] following oral administration of CUT and a novel P. Melo nanosuspension (MP-NPs) in rats.MethodsThe plasma concentrations of these cucurbitacin triterpenoids were quantified through ultra‐performance liquid chromatography-tandem mass spectrometry (UHPLC‐MS/MS). A selective, simple, and sensitive UHPLC‐MS/MS method was developed using the positive ion mode for multiple reaction monitoring analysis. The chromatographic column used was Waters Acquity HSS T3 (1.8 μm, 2.1 × 100 mm), the column temperature was 35 °C, the flow rate was 0.3 mL/min, the injection volume was 5 μL, and the mobile phase was a gradient elution of water (A) and methanol (B). The intra‐ and inter-day precision for all analytes was <13%, and accuracy ranged from −6.41% to −4.01%ResultsAccording to the pharmacokinetic results, when the two rat groups were orally administered with the same dose of CUT and MP-NPs, the elimination half-life (T1/2) of CuD and CuE was longer than that of CuB, indicating slower elimination. Compared with the CUT group, the triterpenoids in the MP-NPs group reached the maximum plasma concentration (Cmax) within 2 h, and both Cmax and the area under the plasma concentration increased significantly.DiscussionThe MP-NPs formulation significantly enhanced the oral bioavailability of cucurbitacin triterpenoids compared to conventional CUT. These findings underscore the potential of nanosuspension technology in improving the pharmacokinetic profile of cucurbitacin-based therapeutics. This study provides valuable insights for further development and clinical application of cucurbitacin nanosuspensions.